IMPLEMENTATION OF THE ULAR TANGGA EDUCATIONAL GAME TO IMPROVE ISLAMIC RELIGIOUS EDUCATION LEARNING INTEREST OF THIRD-GRADE STUDENTS AT STATE ELEMENTARY SCHOOL 1 PANICAN - Siti Fazriyah; Afri Yaningsih; Nesa Fadiyah; Fahar Fathoni; Fiki Danisworo (UIN Antasari Banjarmasin, 2026)
Abstract : Learning is the process through which students acquire new knowledge and serves as the core of education. The learning process can produce optimal outcomes when supported by a high level of learning interest. However, students’ interest in learning has continued to decline across various levels of education. One of the contributing factors is the use of less appropriate teaching methods and the lack of adequate school facilities. This study aimed to examine the learning interest of third-grade students at STATE ELEMENTARY SCHOOLegeri 1 Panican through the implementation of a learning method that differed from those previously used. The study employed a qualitative approach with a case study method. The findings revealed a clear improvement in students’ learning interest. This was reflected in the high level of enthusiasm and active participation demonstrated by students throughout the learning process. Through the implementation of the Islamic Religious Education educational game “Ular Tangga Tahan Lapar”, students were encouraged to understand and recall the material that had previously been delivered by the teacher. This more interactive and enjoyable learning approach helped students become more motivated, creative, and better able to understand the learning material. Keywords : Learning interest; Learning methods; Educational games; Ular Tangga; Effectiveness.